Spiegare e argomentare.
(x^2 - 1)/x^2= 1 - 1/x^2
Quindi:
∫((x^2 - 1)/x^2) dx =
=y = F(x)= x + 1/x + c
{y = 0
{x + 1/x + c = 0
Risolvo: (x^2 + c·x + 1)/x = 0
x^2 + c·x + 1 = 0
condizione di tangenza: Δ = 0
c^2 - 4 = 0---> c = -2 ∨ c = 2
x + 1/x - 2 = 0
y = 0 : x = 1
{y = x + 1/x - 2
{y = (x^2 - 1)/x^2
Risolvo il sistema ed ottengo:
[x = 1 ∧ y = 0, x = √2 + 1 ∧ y = 2·√2 - 2, x = 1 - √2 ∧ y = - 2·√2 - 2]
Da cui i punti interessati:
[1, 0]
[√2 + 1, 2·√2 - 2]
(x^2 - 1)/x^2 - (x + 1/x - 2) =
=- (x^3 - 3·x^2 + x + 1)/x^2
A = ∫(- (x^3 - 3·x^2 + x + 1)/x^2) dx valutato da
x=1 ad x = √2 + 1
per x = √2 + 1
- LN(√2 + 1) - (√2 + 1)^2/2 + 3·(√2 + 1) + 1/(√2 + 1)=
=- LN(√2 + 1) + 3·√2 + 1/2
per x = 1 :
- LN(1) - 1^2/2 + 3·1 + 1/1=
=7/2
A = - LN(√2 + 1) + 3·√2 + 1/2 - 7/2 =
= - LN(√2 + 1) + 3·√2 - 3